La complejidad de los procesos de reestructuración socioespacial de las ciudades intermedias: persistencia y cambio en la ciudad de Puerto Montt (Chile) - Escolano Utrilla, Severino; Ortiz Véliz, Jorge (Anales de Geografía de la Universidad Complutense, 2004)
This paper deals with some effects associated with the processes of urban restructuring in Puerto Montt (Chile). We have particularly explored the transformations in the model of densities of population, and in the physical, functional and sociospatial structures, taking place now. The industrial conglomerate related to the fishing sector, worldwide, is te main factor that has boosted the general process of urban restructuring. The changes are similar to those of other intermediate cities of she urban Chilean system. Nevertheless. in Puerto Montt these changes appear with moderate intensity. In general, the following interrelated trends are identified: increasing fragmentation of the physical space and in the model of densities of population, formation of nodes of centrality in the periphery, and increasing polarization of patterns of spatial segregation.